2019
DOI: 10.1590/s0102-053620190310
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of production and quality traits in interspecific hybrids of ornamental pepper

Abstract: The cultivation of potted peppers as ornamental plants has increased considerably throughout the planet. In Brazil, this crop is more recent and still lacks cultivars. In order to increase the available variability and obtain new cultivars, the interspecific hybridization is very useful in add a desirable attribute that occurs in one species to another species, resulting in a new cultivar of agronomic interest. The objective of this study was to characterize parents and interspecific hybrids based on 27 quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 20 publications
1
9
0
2
Order By: Relevance
“…Of the studied traits, the ones that most contributed to genetic divergence among the evaluated progenies were leaf length (11.1%), pedicel length (9.1%), largest fruit diameter (8.3%), placenta length (7.8%), plant height (7.1%), number of fruits (6.6%), and first bifurcation height (6.4%) (Figure 1). These results can assist in the selection of superior progenies and genotypes, attributing importance to the referred traits in the selection of ornamental peppers (NASCIMENTO et al, 2019). These traits that showed the greatest contributions demonstrated that, even in F2:3, there is still much variability, and these traits should be considered for discriminating between the progenies.…”
Section: Resultsmentioning
confidence: 86%
See 2 more Smart Citations
“…Of the studied traits, the ones that most contributed to genetic divergence among the evaluated progenies were leaf length (11.1%), pedicel length (9.1%), largest fruit diameter (8.3%), placenta length (7.8%), plant height (7.1%), number of fruits (6.6%), and first bifurcation height (6.4%) (Figure 1). These results can assist in the selection of superior progenies and genotypes, attributing importance to the referred traits in the selection of ornamental peppers (NASCIMENTO et al, 2019). These traits that showed the greatest contributions demonstrated that, even in F2:3, there is still much variability, and these traits should be considered for discriminating between the progenies.…”
Section: Resultsmentioning
confidence: 86%
“…), and also as ornamental plants (RÊGO; RÊGO, 2016;. Furthermore, peppers are autogamous species easily propagated by seeds, with short vegetative phases and high aesthetical value (RÊGO et al, 2012;RÊGO;RÊGO, 2018;NASCIMENTO et al, 2019).…”
Section: Introductonmentioning
confidence: 99%
See 1 more Smart Citation
“…Knowledge of genetic diversity provides valuable information for germplasm resources management required in breeding programs [49], [50]. Crossbreed over species is needed to expand genetic diversity [1], [51] and to promote better production and improve resistance to biotic and abiotic stress [52].…”
Section: F Rapd Profilingmentioning
confidence: 99%
“…The Federal University of Paraíba (UFPB) has developed in the last few years an improvement program for ornamental pepper plants whose purpose is the development of new varieties, based mostly on hybridization, generating segregating populations and allowing for the improvers to select superior genotypes, with desirable characteristics for in-pot cultivation (Silva Neto et al, 2014;Rêgo et al, 2015a;Mesquita et al, 2016;Lima et al, 2019;Fortunato et al, 2019;Nascimento et al, 2019;Pessoa et al, 2019). In this perspective, the study of the genetic diversity among genotypes in segregating Rev.…”
Section: Introductionmentioning
confidence: 99%